Bibliometric analysis of youth myocardial infarction research (1980–2023) - Fu, Yang; Han, Qi; Wang, Fei; Dong, Xiuyun (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCardiovascular diseases include myocardial infarction, a high mortality disease. Myocardial infarction patients are becoming younger, typically defined as patients under 45 years of age. This study analyzes the relevant papers on myocardial infarction in youth in the Web of Science Core Collection (WoSCC) between 1980 and 2023.MethodsIt uses bibliometric methods to systematically understand the current status and development trend of research in this field. We searched the WoSCC between 1980 and 2023 for research papers and reviews on myocardial infarction in youth. We set the screening criteria for language as English and used tools such as Citespace, SCImago Graphica, and VOS Viewer to analyze the selected literature exhaustively. This comprehensive approach helped us gain a comprehensive understanding of research hotspots, academic partnerships, and trends in the field.ResultsFrom the WoSCC, we identified 790 publications related to myocardial infarction in youth. First, the United States, Italy, and China are major contributors to international cooperation. The United States plays a vital bridging role. Next, in the scholars' combined contribution power analysis, Krumholz and Donfrio were the key contributors in this field. In addition, popular research directions are based on age. As a result of the literature cluster analysis, we found that myocardial infarction in youth is associated with gender, smoking, coagulation factors, apolipoproteins, and gene polymorphisms.ConclusionThis is the first comprehensive bibliometric study of myocardial infarction in youth. It aims to examine the current status and trends in myocardial infarction in youth. As a result, the study results will provide researchers with an overview of emerging trends.